First-Generation SARS-CoV-2 Vaccines: A Comparative Analysis between Vaccinated and Unvaccinated Hospitalized Patients Infected with SARS-CoV-2 - Basnet, A.; Tamang, B.; Pokhrel, N.; Khadka, S.; Shrestha, M. R.; Ghimire, S.; Prajapati, R.; Thapa, S.; Duwal Shrestha, S. K.; Chand, A. B.; Amatya, I.; Rai, S. K. (Kathmandu University Medical Journal, 2022)
Background Severe acute respiratory syndrome corona virus-2 (SARS-CoV-2) variants, which have emerged due to several mutations in spike protein, have a potential to escape immune protection provided by the first-generation vaccines, thereby resulting in breakthrough infections. Objective To identify the socio-demographic factors, clinical features, and outcomes in both vaccinated and unvaccinated hospitalized patients infected with SARS-CoV-2. Method Socio-demographic details, clinical features, and the outcomes among fully vaccinated (double for Covishield/AstraZeneca and BBIBP-CorV and single for Janssen), partially vaccinated, and unvaccinated hospitalized patients with coronavirus disease of 2019 (COVID-19) were collected and analyzed using SPSS version 17. Result Among the hospitalized COVID-19 patients (n=299), 175 (58.5%) patients received a single-dose, 82 (27.4%) double-dose, and 124 (41.5%) did not receive any dose of the COVID-19 vaccines. The risk of SARS-CoV-2 infection when compared between vaccinated and unvaccinated patients was found to be associated among professional degree holders (23.4% versus 9.7%) (p<0.05), professional workers (43.4% vs. 25.0%) (p<0.05), hospitalization to general ward (76.6% vs. 72.6%) (p<0.05), and presence of multiple symptoms (≥3) (86.8% vs. 75.0%) (p>0.05) and comorbidities (≥2) (15.5% vs. 13.7%) (p>0.05). Despite such approximate incidences, the risk of in-hospital mortality among the vaccinated patients was reduced (0.6% vs. 3.2%) (p>0.05), when compared to the unvaccinated patients. The risk of in-hospital mortality was associated with the older age and the presence of multiple comorbidities including bronchial asthma, diabetes, and hypertension. Conclusion Full or partial vaccination against the SARS-CoV-2 variants of concerns might be effective in preventing in-hospital mortality among COVID-19 patients.